2021
DOI: 10.1101/2021.06.30.449460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partners in space: Discordant population structure between legume hosts and rhizobium symbionts in their native range

Abstract: Coevolution is predicted to depend on how the genetic diversity of interacting species is geographically structured. Plant-microbe symbioses such as the legume-rhizobium mutualism are ecologically and economically important, but distinct life history and dispersal mechanisms for these macrobial and microbial partners, plus dynamic genome composition in bacteria, present challenges for understanding spatial genetic processes in these systems. Here we study the model rhizobium Ensifer meliloti using a hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 128 publications
(213 reference statements)
0
4
0
Order By: Relevance
“…Study system. Full details are provided in Riley et al (52) and SI Methods. Ensifer (formerly Sinorhizobium) meliloti is an Alphaproteobacteria that forms symbiosis with various Medicago spp., fixing atmospheric N in return for plant photosynthate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study system. Full details are provided in Riley et al (52) and SI Methods. Ensifer (formerly Sinorhizobium) meliloti is an Alphaproteobacteria that forms symbiosis with various Medicago spp., fixing atmospheric N in return for plant photosynthate.…”
Section: Methodsmentioning
confidence: 99%
“…DNA isolation, whole-genome sequencing, and variant calling. Detailed methods are provided in Riley et al(50), and SI Methods. We obtained DNA from each of the 191 rhizobium isolates, sequenced their full genomes including the chromosome and two symbiosis plasmids, used a common reference-based assembly pipeline to align sequences and call single nucleotide polymorphisms (SNPs), and filtered the resulting SNPs based on sequence quality, depth, minor allele frequency, and missingness, resulting in a total of 36,526 filtered SNPs.…”
mentioning
confidence: 99%
“…For example, by experimentally-evolving strains of S. meliloti on five M. truncatula lines, Batstone et al (66) found that local adaptation was largely governed by conditional neutrality (beneficial on local host, neutral on non-local hosts) or mildly deleterious effects on non-local hosts, likely due to drift in the local context. Yet, in nature where rhizobium population sizes are much larger and more diverse, and gene flow is present, the extent to which local adaptation occurs has rarely been tested but might be unlikely (28, 111, 112), except for populations differentiated by strong ecological gradients (e.g., 102). Moreover, the host genotypes used in our study, DZA and A17, are unlikely to share an evolutionary history with our strains, and so it remains unclear whether stronger trade-offs (and less conditional neutrality) would be present if our strains shared an evolutionary history with the host lines being tested.…”
Section: Discussionmentioning
confidence: 99%
“…Previous mapping efforts in the legume-rhizobium system have focused on the HapMap collections, which maximize diversity using a range-wide sample. Our study focuses on the segregating natural variation at a smaller geographic scale, a scale at which pSymA and pSymB segregate (107); thus the G × G-driven variation we find here would be available to local evolutionary and/or coevolutionary processes. G × G interactions for fitness outcomes have long been of interest in the legume-rhizobium symbiosis (25,116,28,97,117) and other interactions (118,119,120) (132,133,134,135).…”
Section: Universal Associations Highlight Transport Functions and Secretion Systemsmentioning
confidence: 99%